Design and optimization of ship propulsion systems for ‎improved efficiency - Palanivelu, Rajendran; Raj, Yeshwanth (International Journal of Basic and Applied Sciences, 2025)
New rules due to contemporary environmental issues and high and volatile fuel prices are the main reasons for reducing operating expenses with more environmental friendliness. Reducing fuel consumption is the main reason. Due to current economic constraints and worldwide regulations, reducing energy usage and saving even more on ship fuel is needed. From an industry point of view of the ocean, there are technical solutions and standards for operating ships in energy-efficient modes. But there are also other intricate problems facing the shipping industry nowadays that are choosing the best technique and keeping it under continuous surveillance during a passage. The fuel saving could be lower than anticipated because of real-time environmental conditions like sea state and weather, even if the route of the ship is optimized. As per the Ship Energy Efficiency Management Plan (SEEMP), the aim of this project is to create and construct a Decision support System (DSS) for optimizing energy utilization with the help of real-time decision support and thereby improving energy efficiency in shipping operations. Real-time energy monitoring and making optimal decisions during operation of the ships are also facilitated through the DSS. In developing the DSS, which will help improve energy use in ship operations when at sea and on land, we shall choose an energy model software and optimization method from existing literature.